Experiential Learning Model on Entrepreneurship Subject to Improve Students’ Soft Skills - Naufalin, Lina Rifda; Dinanti, Aldila; Krisnaresanti, Aldila (Dinamika Pendidikan, 2016)
This research aims to improve students’ soft skills on entrepreneurship subject by using experiential learning model. It was expected that the learning model could upgrade students’ soft skills which were indicated by the higher confidence, result and job oriented, being courageous to take risks, leadership, originality, and future-oriented. It was a class action research using Kemmis and Mc Tagart’s design model. The research was conducted for two cycles. The subject of the study was economics education students in the year of 2015/2016.  Findings show that the experiential learning model could improve students’ soft skills. The research showed that there is increased at the dimension of confidence by 52.1%, result-oriented by 22.9%, being courageous to take risks by 10.4%, leadership by 12.5%, originality by 10.4%, and future-oriented by 18.8%. It could be concluded that the experiential learning model is effective model to improve students’ soft skills on entrepreneurship subject. Dimension of confidence has the highest rise. Students’ soft skills are shaped through the continuous stimulus when they get involved at the implementation.